INTERNALISASI NILAI-NILAI SOSIO-KULTURAL BERBASIS ETNO RELIGI DI MASYARAKAT WANNAS KAMPUNG KOYA KOSO PAPUA - Arifa, Neswara Alda; Karman, Abdul; Ulfain, Ulfain (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to find out about the deepening of socio-cultural values that exist in the Wannas community of Koya Koso village based on ethno-religion caused by the integration of the Bugis tribe in it. The research seeks to reveal an ethno-religious group which is an ethnic group of people whose members are also united by different religious and ethnic backgrounds. The concept of socio cultural values is an inculcation of a way of life of respect, sincerity, and tolerance for the diversity of cultures that live in the midst of a plural society. The research method used is field research or field research with a qualitative approach with data sources from interviews, observations, and documentation. The results of the study describe the conditions that exist in the Wannas hamlet, Koya Koso village among the indigenous Papuans, migrant communities from the Bugis tribe of South Sulawesi are able to adapt to the surrounding environmental conditions and understand the local culture but their is no significant cultural acculturation, this illustrates that integration socio-cultural values of respect for differences, religious tolerance, and social coherence.